Public service innovation (free medicine program for disadvantage communities in Pasaman Barat District) - Sonda Winari; Aldri Frinaldi (Enrichment : Journal of Management, 2023)
This study aims to explain a public service innovation in the health sector in West Pasaman district. This research is important so that readers can obtain information related to the existence of public service innovations in the form of free medical treatment for underprivileged people in West Pasaman Regency. This study uses a qualitative-descriptive approach. This free medical treatment program is intended for underprivileged people who do not have BPJS. This program is a collaboration between the government and health services in West Pasaman district. The innovation in this service is due to its uniqueness with the free medical treatment system for the people of West Pasaman who do not have BPJS. The purpose of this public service innovation, especially in the health sector, is to create a healthy community in West Pasaman district. The implementation of the free medical treatment program in West Pasaman district is said to be quite good, this is evidenced by the satisfaction of 95% of West Pasaman residents who have received medical treatment.